Seat arrangement problems - Longani V. (2017)
© 2016 by the Mathematical Association of Thailand. All rights reserved. Let there be n students, and n row seats. For n days, a seat is arranged for each student on each day, and each student is required to sit on different seat on each of the n days. Also for these n days, it is required that each student shall has one chance to sit next to every other (n-1) students on one of his side, and shall has one chance to sit next to every other (n-1) students on the other one of his side. In this paper, we provide sufficient conditions and an algorithm for the arrangements.